Commodifying Hadith: Social Media and The Caliphate Narrative — A Case Study of @Muslimahminangrindusyariah - Afandi, Yusuf; Qatrunnada, Dhia; Efendi, Efendi; Sabri, Yuli; Hamdanus, Hamdanus (Universitas Islam Negeri Imam Bonjol Padang, 2024)
This article aims to analyze the commodification of hadiths to strengthen the ideological narrative of the caliphate on the Instagram account @muslimahminangrindusyariah. This Instagram account promotes caliphate ideas through posts, reels, and livestreaming, utilizing appealing graphic visuals. This qualitative research employs qualitative content analysis to examine how certain hadiths are selected and interpreted to frame the caliphate narrative as the sole solution to various issues the Muslim community faces. As a social media platform, Instagram enables the widespread dissemination of ideologies, allowing actors to present hadiths to support their political views freely. The study's findings reveal that the @muslimahminangrindusyariah account consistently uses hadiths to emphasize the obligation of Muslims to establish a caliphate, portraying it as the solution to social, political, and economic problems. The hadiths used are not diverse, with only one being repeatedly utilized across multiple posts—specifically, the hadith regarding collective ownership of natural resources, which is argued to only be achievable through a caliphate system. This research offers novelty in the study of hadiths and digital da'wah in Indonesia, focusing on the segment of Muslim women and the use of social media to disseminate caliphate ideology. These findings contribute to a broader understanding of the role of social media in shaping ideological and political discourses among Muslims.